Development of two TaqMan real-time reverse transcription-PCR assays for the detection of severe acute respiratory syndrome coronavirus-2 - Liu, Yiwei (Biosaf Health, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, China, was caused by a novel coronavirus (CoV), named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The rapid detection of viral nucleic acids is critical for the early identification of infected cases. We have developed two TaqMan real-time reverse transcription-PCR assays to detect SARS-CoV-2. The designed primers target the nucleocapsid (N) and open reading frame (ORF) 1b gene regions, where the probes discriminate SARS-CoV-2 from other human and animal CoVs. The sensitivities are one genomic copy per reaction for the N gene assay and ten copies for the ORF 1b gene assay. The overall linear detection ranges are 1–10(6) and 10–10(6) copies per reaction for the N gene assay and the ORF 1b gene assay, respectively. Surveillance of 23 suspected COVID-19 patients demonstrated that SARS-CoV-2 could be detected from 100% (23/23) and 62.5% (16/23) of clinical specimens by the N gene assay and the ORF 1b gene assay, respectively. All of the samples not detected by the ORF 1b gene assay were throat swabs, indicating a lower viral load in the upper respiratory tract and the relatively lower sensitivity of the ORF 1b gene assay. The assays developed in the present study offer alternative diagnostic tests for COVID-19.